P123-CoMgAl composite for sustainable and high-conversion epoxide ring-opening polymerization - Cao, Xiaoyan; Xu, Xiao; Wu, Gongming; Gu, Zhenggui (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2025)
The ring-opening polymerization lays the foundation for synthesizing polypropylene glycol. Nevertheless, homogeneous alkali catalysts usually require complex post-treatments, hindering green synthesis and environmental sustainability. Here, we studied a heterogeneous epoxide polymerization method based on a P123-modified nanocomposite layered double oxide (CoMgAl-LDO(P123)). Thereafter, the composition, crystal structure, morphology, and thermal stability of the catalyst were characterized through SEM, XRD, FTIR, XPS, BET, and TG-DTG techniques. The results indicated that due to the designable and self-assembled P123 micelles, CoMgAl-LDO(P123) generated consistent mesoporous channels and a larger specific surface area. The introduction of cobalt enriched the alkaline sites on the CoMgAl-LDO(P123) surface. In the synthesis of small molecular weight poly(propylene glycol) (i.e., number average molecular weight less than 500), the catalytic performance of CoMgAl-LDO(P123) for the conversion of propylene oxide reached 96.3% under the optimal reaction conditions, which was superior to that of other catalysts. Our strategy addresses the trade-off issue that alkali catalysts faced in terms of sustainability and operational complexity, holding great promise in green chemistry.